2021
DOI: 10.14309/ajg.0000000000001397
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Placebo Response and Its Determinants in Functional Dyspepsia

Abstract: INTRODUCTION: Placebo response rates are relatively higher in clinical trials of disorders of brain-gut interaction. However, placebo response in functional dyspepsia (FD) has not been well described. Minimizing placebo response is important in drug development. We therefore conducted a meta-analysis to determine placebo response in trials for FD and to identify factors affecting placebo response rates. METHODS: PubMed, EMBASE, and the Cochrane Central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
2
7
2
Order By: Relevance
“…This meta‐analysis was prompted by the fact that only very limited data are available regarding the pooled placebo response rate and its possible moderators in pharmacological trials in FD. The pooled placebo response rates in this meta‐analysis were in line with the pooled placebo response rate in another recent meta‐analysis 15 . However, approximately half of the included articles in that meta‐analysis had a non‐pharmacological active therapy and varying dosage forms, what probably led to more heterogeneity in their results with larger confidence intervals.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This meta‐analysis was prompted by the fact that only very limited data are available regarding the pooled placebo response rate and its possible moderators in pharmacological trials in FD. The pooled placebo response rates in this meta‐analysis were in line with the pooled placebo response rate in another recent meta‐analysis 15 . However, approximately half of the included articles in that meta‐analysis had a non‐pharmacological active therapy and varying dosage forms, what probably led to more heterogeneity in their results with larger confidence intervals.…”
Section: Discussionsupporting
confidence: 84%
“…The previously identified predictors of the placebo response rate, that is, an association of a higher BMI, 16,17 a nonsmoking status, 16 low symptom severity at baseline, 16 symptom progression during run-in, 16 and a longer study period 15 with a higher placebo response, were not completely in line with the results of this metaanalysis. The effect of smoking status and symptom progression during run-in could not be evaluated, because of incomplete reporting of these factors in the individual trials.…”
Section: Ta B L Econtrasting
confidence: 57%
See 1 more Smart Citation
“…These findings are consistent with a previous meta-analysis of 58 functional dyspepsia clinical trials 4 in which an average 44% placebo response was reported for symptom improvement and 15.6% for complete symptomatic relief. Similar rates have also been found in irritable bowel syndrome where a 2010 meta-analysis of 73 clinical trials reported a 37.5% placebo response rate for symptomatic improvement, 5 while Ballou 6 and colleagues reported a 29% placebo response rate in chronic constipation when abdominal pain was the endpoint and Nee 7 and colleagues reported pooled placebo response rate from 13% to 26% depending on which endpoint was considered.…”
Section: Overvie Wsupporting
confidence: 92%
“…An impediment to evaluating therapies is the high rate of placebo response, estimated in a recent meta-analysis to be 44% meeting response criteria and 15% when complete relief was the end point (5). Because a treatment effect for an intervention is estimated as the difference between the change/response observed among individuals receiving an experimental therapy and that observed among individuals receiving a placebo (6), a high placebo response can lead to low estimates of treatment effect size even if the treatment is itself associated with a strong and consistent reduction in symptoms.…”
Section: Introductionmentioning
confidence: 99%